Behavioural determinants of obesity. - Rennie, K; Johnson, L; Jebb, SA (2005)
Obesity in children arises from a complex interplay between genetic susceptibility and behaviour, primarily relating to dietary habits and physical activity. Evidence for specific behavioural factors that promote or protect against excess weight gain in children is more limited than in adults, and the effects of growth and development are not clear. A number of behavioural risk factors has been postulated, including diets with a high energy density, high consumption of sugar-sweetened beverages, large portion sizes, eating patterns, high levels of sedentary behaviour and low levels of physical activity. However, most evidence is derived from cross-sectional studies which frequently yield conflicting results. More prospective studies with accurate measures of exposures and outcomes in terms of body composition are needed to provide more robust evidence on which to base interventions to achieve long-term behavioural change and prevent excess weight gains in children.